CASE STUDY: COLISEPTICEMIA IN A 1-MONTH-OLD PIGLET IN TARO VILLAGE, GIANYAR, BALI - Fira Aulia Aryani; Ni Wayan Helpina Widyasanti; I Ketut Berata; Ida Bagus Made Oka; Tjokorda Sari Nindhia (Buletin Veteriner Udayana, 2026)
Pig farms play an important role in the socio-cultural life of communities, but some of them are intensively managed with poor biosecurity and health management practices, as well as traditional and unhygienic husbandry practices, thereby potentially increasing the risk of health problems in livestock. Colisepticemia is a disease caused by infection with pathogenic Escherichia coli, which primarily affects piglets from the neonatal to post-weaning period. The subject of this case study was a one-month-old Landrace piglet from a smallholder farm in Taro Village, Tegallalang District, Gianyar Regency, Bali. This study aimed to determine the cause of death of the piglets based on epidemiological data, clinical examination, anatomical pathology, histopathology, bacteriology, and parasitology. Epidemiological data showed a total herd population of 455 pigs, with morbidity of 1.76%, mortality of 1.76%, and a case fatality rate (CFR) of 100%. Clinical signs observed in the piglet included anorexia, weakness, vomiting, yellowish-white diarrhea, and inability to stand. The piglet died after showing clinical signs for 16 days. Gross pathological examination revealed congestion in the brain, heart, lungs, liver, kidneys, and intestines, as well as hemorrhage in the trachea, lungs, and intestines. Histopathological examination showed that almost all organs had congestion, hemorrhage, and inflammatory cell infiltration predominantly composed of neutrophils. Bacterial isolation from the lung, heart, liver, and intestines demonstrated growth of Gram-negative Escherichia coli. Parasitological examination using direct smear, sedimentation, and flotation methods yielded negative results for protozoan and helminth infections. Based on these findings, the piglet was diagnosed with colisepticemia.